Analisis Yuridis terhadap Korban Penyebaran Berita Bohong (Hoax) di Media Sosial - Ridho Mubarak; Wessy Trisna (Universitas Medan Area, 2021)
Technological developments make it easier for people to get any information from various social media applications including Instagram, LINE, and Whatsapp, but it is easier for irresponsible parties to consciously spread false information. Social media is different from the mass media which is used to disseminate information and news, this is because social media is not organized or institutionalized. So that if any news broadcast turns out to be fake news (hoax), the mass media can be sued or held accountable for broadcasting hoaxes. This research is a normative empirical legal research which is descriptive analytical in nature, meaning that this research does not only describe by analyzing a situation or symptom, both at a positive legal level but also wants to provide proper regulation (das sollen) and solve legal problems related to hoax crime. The data collected using literature review and document analysis aims to provide an overview of the legal regulations governing these indirect victims. As for the results of the research, it is hoped that efforts should be made by the police to protect the people who are disadvantaged by this hoax.